2016
DOI: 10.1021/acs.organomet.5b00877
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Allyl–Borohydride Lanthanide Complexes: Synthesis of Ln(BH4)2(C3H5)(THF)3 (Ln = Nd, Sm), Characterization, and Reactivity toward Polymerization

Abstract: New mixed allyl−borohydrido lanthanide complexes Ln(BH 4 ) 2 (C 3 H 5 )(THF) 3 (Ln = Nd (1), Sm (2)) could be prepared in good yield by reacting Ln(BH 4 ) 3 (THF) 3 (Ln = Sm, Nd) with 1/2 equiv of Mg(C 3 H 5 ) 2 (THF) x . X-ray structure analysis revealed monomeric structures with two terminal BH 4 ligands, one π-allyl ligand, and three THF molecules. In an assessment of isoprene polymerization, 1 afforded trans-1,4-polyisoprene in good yield, as a single component or in combination with Mg cocatalyst. Both 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…[c] Determined by SEC in THF at 40 °C against polystyrene standards with the correction M n(exp) = M n PS ×0.56, Ð = M w / M n . [d] Taken from reference .…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…[c] Determined by SEC in THF at 40 °C against polystyrene standards with the correction M n(exp) = M n PS ×0.56, Ð = M w / M n . [d] Taken from reference .…”
Section: Resultssupporting
confidence: 78%
“…The synthesis of the neodymium and samarium complexes of the type [RE(BH 4 ) 2 (C 3 H 5 )(thf) 3 ] [RE=Nd ( 4 ) and Sm ( 5 )] was reported in a preliminary work from our group . In this work, we reported that the attempt to substitute one of the borohydrides groups of [Nd(BH 4 ) 3 (thf) x ] by an allyl ligand by using the classical Grignard reagents (C 3 H 5 )MgX (X=Cl, Br) led to untraceable mixtures, although Taube et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bonnet, Visseaux, and co-workers synthesized the first RE complexes bearing both allyl and borohydride ligands, RE(BH 4 ) 2 (η 3 -C 3 H 5 )(THF) 3 (8 RE , RE = Nd, Sm, Scheme 4) by reacting RE(BH 4 ) 3 (THF) 3 with half an equivalent of Mg(C 3 H 5 ) 2 (L) n (L = THF, dioxane) in THF at room temperature [29]. From 1 H NMR analysis, the allyl moiety appeared as a 1H/2H/2H set of resonances for both 8 RE complexes, revealing no dynamic behavior at the 1 H NMR timescale.…”
Section: Allyl Complexes For the Polymerization Of Isoprenementioning
confidence: 99%